1997
DOI: 10.1002/jor.1100150521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cisplatin chemotherapy on extracortical tissue formation in canine diaphyseal segmental replacement

Abstract: The reconstruction of large bone and joint defects after the resection of malignant tumors remains a major challenge. Chemotherapy has significantly lowered the risk of metastasic disease, but complications associated with reconstructive techniques continue to result in late morbidity. In the present study, biomechanical torsion testing, gait analysis, and histomorphometric and scanning electron microscopic evaluations of 24 dogs were used to examine the effects of preoperative and postoperative administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…For those with a good prognosis, ensuring adjuvant treatment does not interfere with the fixation of the reconstruction could ensure a better outcome, as chemotherapy and radiotherapy may interfere with osteointegration. 7,28,31,32 This theoretical concern, however, has not been documented clinically.…”
Section: Discussionmentioning
confidence: 88%
“…For those with a good prognosis, ensuring adjuvant treatment does not interfere with the fixation of the reconstruction could ensure a better outcome, as chemotherapy and radiotherapy may interfere with osteointegration. 7,28,31,32 This theoretical concern, however, has not been documented clinically.…”
Section: Discussionmentioning
confidence: 88%
“…For those with better prognosis, avoiding early complications that can interfere with adjuvant treatment and insuring longevity of the construct is of paramount importance. 8,35,36 The use of cemented implants has the additional advantage of immediate stability of the construct, allowing immediate full weightbearing and rehabilitation of the affected limb.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggestive that chemotherapeutic agents have an adverse effect on normal physiological bone turnover, especially osteoblastic activity, and would also be expected to alter fracture-healing and bone-allograft incorporation by these same mechanisms. 18 In the second publication of the study, now turned to a biomechanical and histologic analysis and observing the effects of chemotherapy either preoperatively or postoperatively, Young et al 19 observed that postoperative chemotherapy resulted in less bone formation, but extracortical capsule formation was not inhibited, whereas preoperative chemotherapy did not alter the formation of a new bone. Animal experiments are difficult to translate into a clinical setting, but formation of periimplant connective tissue would be detrimental to the osseointegration of dental implants.…”
Section: Discussionmentioning
confidence: 96%